Effect of breed, sex and litter size on growth and meatiness and fattiness in vivo in lambs - Martin Hošek; Leona Konečná; Jan Kuchtík; Radek Filipčík (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
The main aim of the study was the evaluation of the effects of breed (Suffolk, Merinoladschaf, Oxford Down and Charollais), sex and litter size (singles, twins and triplets) on growth. The study was carried out on the farm in Žabčice in 2007. Within the frame of evaluation of meatiness and fattiness in vivo in lambs the following ultrasound measurements were carried out: depth of musculus longissimus lumborum et thoracis (Dm.l.l.t.) and fat thickness (FT). Ultrasound measurements was done between last pectoral and first lumbar vertebrae after tease out of wool, by ultrasound Aloka SSD 500 with 5 MHz linear probe. The breed had not a significant effect on all growth parameters under study. On the other hand the sex and the litter size had a significant effect on some growth parameters under study, whereas both these factors had a significant effect on live body weight at 100 days of age of lambs and on daily gain in the period from 30 to 70 days of age. The litter size had a significant effect on Dm.l.l.t. of lambs at the age of 70 and 100 days. On the other hand the breed had a signifcant effect on Dm.l.l.t. only at the age of 100 days. The breed, sex and litter size had a significant effect on FT of lambs at the age of 70 days. On the other hand all the factors under study had not significant effect on FT of lambs at the age of 100 days.